Best Practices in Managing Resource-Limited Research: The Case of Comprehensive Analysis of the Poverty Situation in the Southern Tagalog Island Provinces - Mani, Merian; Sespene, Jeter; Aromin, Erlinda; Fetalvero, Eddie; Foja, Lou (Romblon State University Research Journal, 2011)
The paper presents the researcher’s experience in managing and completing a qualitative research on the comprehensive analysis of the poverty situations in Region IV-B known as the MIMAROPA Region under very limited time and budget. Constrained with the issues, the researchers employed various strategies to complete the research study. Along the process, best practices were discovered. These experiences gave birth to a new R&D management framework the “Community In Vitro and In Vivo Development Approach”, the novelty of this study. The Key Informant Interview (KII) and Focus Group Discussion (FGD) are the main tool used in gathering data to draw the real picture of the poverty situations in the five island provinces (Mindoro Occidental, Mindoro Oriental, Marinduque, Romblon and Palawan) in region IV-B. The respondents of the study were from two least progressive municipalities in each province which were identified based on the National Economic and Development Authority classification and that of the Peace and Equity Foundation poverty mapping in 2006. Eleven (11) Key Informants were purposely identified to gather sufficient data. Three Focus Group Discussions were conducted in each municipality from multi-sector groups, and with special groups like; the inmates, rebel returnees, indigenous people and the women’s organization. The whole new approach yielded very interesting and relevant results thus showing the efficiency and effectiveness of the new R&D management framework.